AMHY and sex determination in egg-laying mammals - Linda Shearwin-Whyatt; Jane Fenelon; Hongshi Yu; Andrew Major; Zhipeng Qu; Yang Zhou; Keith Shearwin; James Galbraith; Alexander Stuart; David Adelson; Guojie Zhang; Michael Pyne; et al. (Genome Biology)
Abstract Background Egg-laying mammals (monotremes) evolved multiple sex chromosomes independently of therian mammals and lack the sex-determining gene SRY. The Y-localized anti-Müllerian hormone gene (AMHY) is the candidate sex-determination gene in monotremes. Here, we describe the evolution of monotreme AMHX and AMHY gametologues and for the first time, investigate their expression during gonad sexual differentiation in a monotreme. Results Monotreme AMHX and AMHY have significant sequence divergence at the promoter, gene, and protein level, likely following an original allele inversion in the early stages of monotreme sex chromosome differentiation but retaining the conserved features of TGF-β molecules. We show that the expression of sexual differentiation genes in the echidna fetal gonad, including DMRT1 and SOX9, is significantly different from that of therian mammals. Importantly, AMHY is expressed exclusively in the male gonad during sexual differentiation consistent with a role as the primary sex-determination gene whereas AMHX is expressed in both sexes. Experimental ectopic expression of platypus AMHX or AMHY in the chicken embryo did not masculinize the female urogenital system, as does chicken AMH, a possible result of mammalian-specific changes to AMH proteins preventing function in the chicken. Conclusions Our results provide insight into the early steps of monotreme sex chromosome evolution and sex determination with developmental expression data strongly supporting AMHY as the primary male sex-determination gene of platypus and echidna.